Kedudukan Anak Luar Kawin yang Diangkat oleh Kakeknya di Desa Batukaang, Kecamatan Kintamani, Kabupaten Bangli - Ni Nyoman Oktaviani; Ketut Sukadana; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2020)
Children born out of wedlock are children born to a woman who does not have a legal marriage relationship with a man who has made her give birth to the child. The child does not have a perfect position in the standpoint of the law like a legitimate child in general. The birth of a child is crucial in every family. In terms of family life, children are descendants of the next generation so a child has the right to life and identity as an effort to protect the law. The problem how the adoption of a child born beyond official marriage by his grandfather in Desa Batukaang, the Sub-district of Kintamani, Bangli Regency is executed and what is the inheritance system for such an adopted child in Batukaang Village, Kintamani District, Bangli Regency? The child was appointed by his own grandfather and the reason for the appointment was that the adoptive grandfather did not have a son. The type of research used in this research is an empirical study with a juridical-sociological approach. Types of data are primary data and secondary data, collected through interview and literature review. The procedure for the adoption of the child execution is through customary or noetic way, which is to carry out extortion ceremonies where offerings are religiously and legally made and the child is legally made as a legitimate child in general. Ultimately, the child is legitimate to be the child of the adopting grandfather both in a customary and inheritance legal system, the child inherits all inheritance from the grandfather.